Atmospheric pressure matrix‐assisted laser desorption/ionization mass spectrometry of engine oil additive components. (6th March 2022) - Ramopoulou, Lamprini; Widder, Lukas; Brenner, Josef; Ristic, Andjelka; Allmaier, Günter
Abstract : Rationale: The efficiency of lubricants strongly depends on the content of functional additives. In order to assess the chemical and structural changes taking place in the lubricating oil and its additives during operation, it is essential to develop a method for simple and prompt analysis. Methods: Two single additives as well as a fully formulated engine oil were analysed using an atmospheric pressure matrix‐assisted laser desorption/ionization (AP‐MALDI) source coupled to a linear trap quadrupole Orbitrap XL hybrid tandem mass spectrometer and compared with results obtained by means of electrospray ionization (ESI) including additional low‐energy collision‐induced dissociation (LE‐CID). The identification of additives directly from technical surfaces was simulated by using steel substrates as AP‐MALDI targets with varying roughness. Results: After assessment and selection of the most suited AP‐MALDI matrix it was found that pure additives such as calcium sulfonate and zinc dialkyldithiophosphates (ZDDPs) could well be identified with abundant signal intensity based on their elemental composition. Molecular identification was corroborated by LE‐CID in ESI mode. Additionally, additives present in the fully formulated commercial oil such as ZDDPs and salicylates could be reliably identified based on the elemental composition of the deprotonated molecules by means of the Orbitrap unit on different substrates including steel surfaces with high roughness. Conclusions: AP‐MALDI is an efficient technique for determination of lubricant additives directly from commercial oil blends. Identification of additive components was also achieved on steel surfaces with high roughness as applied in tribological systems and thus it is expected that it will be possible to assess additive degradation in real applications, enabling more effective and timely maintenance measures.